دراسة تأثير النمو العمراني على شكل الفضاءات العمومية للمدن الصحراوية باستخدام تقنية بناء الجملة الفراغية ( SPACE SYNTAX ) (دراسة مقارنة لثلاث أحياء بمدينة ورقلة) - شاهد, علي حيدر; علقمة, جمال (Courrier du Savoir; No 26 (2018): Courrier du Savoir, 2018)
The physical changes that took place in Ouargla as a desert city were not only in terms of broad regional expansion, but also through internal material transformations. Urban space and public spaces have increased significantly in the city of Ouargla in the past three decades. The proportion of public spaces of the total land area for modern neighborhoods is more than 60%, which does not reflect the awareness of the factors affecting the urban environment of the desert areas of environmental dimensions Climate, social and economic. This is due to the urbanization policies adopted and the adopted architectural patterns as well as the embodied urban structures. While the other images are quite different for this where the vacant land is exploited and transferred to the built areas, Parks and playgrounds to parking and expansion of private buildings. The massive population growth has had an impact on city streets, urban style, open spaces, environmental housing and various service sectors. The current research is an attempt to study the transformation of the urban form of Ouargla in this regard by studying its public spaces through comparing models of neighborhoods that reflect the prevailing patterns in the city. Furthermore, this study reflects the approaches adopted in responding to the growth of this city by using the Space Syntax Technique of Bill Hillier's spatial analysis of the urban tissues of the city in an objective way in which the degree of interconnection between elements of the textile network can be calculated. This kind of study is useful for analyzing the relationship that existed between the built and unstructured space of the traditional city and the changes that occurred in that relationship during the growth of the city over time.